The Trend of Media Convergence and its Impact in Journalism and Communication Studies - Yang, Yutian (Transactions on Social Science, Education and Humanities Research, 2024)
The trend of media convergence and its impact in the field of journalism and communication studies has become increasingly evident. As information technology rapidly evolves, the boundaries between traditional and new media are becoming blurred. Various media formats are integrating deeply in terms of content, platforms, and channels, bringing unprecedented changes to the realm of news dissemination. The trend of media convergence not only drives innovation in the ways news is communicated but also significantly impacts both the theoretical research and practical applications within journalism and communication studies. In terms of communication methods, media convergence allows news content to be presented in more diversified and personalized ways, meeting the diverse needs of audiences. Cross-platform dissemination and interactive communication are becoming the norm, significantly improving the speed and efficiency of news dissemination. Theoretically, media convergence offers new perspectives and methodologies for journalism and communication studies. The impact of media convergence on news dissemination processes, audience behavior, and communication effects has garnered widespread attention, exploring new laws and characteristics of news dissemination. However, media convergence also presents a series of challenges. Thus, continuous innovation and transformation are needed to adapt to the new communication environment and development needs, promoting the ongoing development and progress of journalism and communication studies.